1977
DOI: 10.1152/ajprenal.1977.232.4.f298
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of renal sodium reabsorption by angiotensin II

Abstract: Various parameters of renal function were studied before, during, and after the infusion of physiological increments of angiotensin II directly into one renal artery of anesthetized dogs. During water diuresis and during antidiuresis induced with exogenous antidiuretic hormone (ADH), angiotensin II consistently reduced UNaV, UKV, and CPAH, and increased the filtration fraction in the infused kidney. Urinary osmolality was increased only in the presence of ADH, while during water diuresis angiotensin II had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…Inhibiting AT 1 receptors markedly increased the FENa in the presence of a modest fall in MAP, suggesting that the increase in FENa can be attributed to the withdrawal of the antinatriuretic effect of Ang II. Indeed, low doses of Ang II are well known to directly increase proximal tubular reabsorption of sodium 9,24,25 and also stimulate distal reabsorption through stimulation of aldosterone secretion. 26 However, since AT 1 blockade also increased RBF and GFR, the increased FENa may have also been due to increased renal interstitial pressure subsequent to the elevation in RBF and GFR.…”
Section: Relative Role Of Ang II Through Its At 1 Receptor Et No Amentioning
confidence: 99%
“…Inhibiting AT 1 receptors markedly increased the FENa in the presence of a modest fall in MAP, suggesting that the increase in FENa can be attributed to the withdrawal of the antinatriuretic effect of Ang II. Indeed, low doses of Ang II are well known to directly increase proximal tubular reabsorption of sodium 9,24,25 and also stimulate distal reabsorption through stimulation of aldosterone secretion. 26 However, since AT 1 blockade also increased RBF and GFR, the increased FENa may have also been due to increased renal interstitial pressure subsequent to the elevation in RBF and GFR.…”
Section: Relative Role Of Ang II Through Its At 1 Receptor Et No Amentioning
confidence: 99%
“…Kimbrough et al 41 have indicated that intra-renal angiotensin II may promote the conservation of salt and water. Johnson and Malvin 43 have suggested that angiotensin II exerts a direct stimulatory effect on tubular sodium reabsorption independent of changes in renal blood flow or glomerular filtration rate. We would like to speculate that the 50% greater PRA values observed in the relatives before, and 33% greater PRA values immediately after, the intravenous sodium loads may have resulted in increased angiotensin II levels, which may have impeded the natriuretic responses of the relatives.…”
Section: -41mentioning
confidence: 99%
“…However as we have not measured renal blood flow in our study we cannot exclude intrarenal haemodynamic changes. Nevertheless it has been demonstrated that low doses of AII can decrease sodium excretion in animals and man without changes in GFR or renal plasma flow (Johnson & Malvin, 1977;Ljungman et al, 1983), and without changing the intrarenal distribution of blood flow in animals (Johnson & Malvin, 1977). Similarly low dose infusion of NA and low frequency renal SNS stimulation in animals can reduce sodium excretion without affecting GFR, renal blood flow or distribution of intrarenal blood flow (Slick et al, 1975;DiBona, 1978;Johnson & Barger, 1981).…”
Section: Discussionmentioning
confidence: 99%